Thiol‐based copper handling by the copper chaperone Atox1. Issue 4 (15th March 2017) - Hatori, Yuta; Inouye, Sachiye; Akagi, Reiko
Abstract: Human antioxidant protein 1 (Atox1) plays a crucial role in cellular copper homeostasis. Atox1 captures cytosolic copper for subsequent transfer to copper pumps in trans Golgi network, thereby facilitating copper supply to various copper‐dependent oxidereductases matured within the secretory vesicles. Atox1 and other copper chaperones handle cytosolic copper using Cys thiols which are ideal ligands for coordinating Cu(I). Recent studies demonstrated reversible oxidation of these Cys residues in copper chaperones, linking cellular redox state to copper homeostasis. Highlighted in this review are unique redox properties of Atox1 and other copper chaperones. Also, summarized are the redox nodes in the cytosol which potentially play dominant roles in the redox regulation of copper chaperones. © 2016 IUBMB Life, 69(4):246–254, 2017